2017
DOI: 10.1021/acs.langmuir.7b02659
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Efficiency of Quantum Dot-Sensitized Solar Cells through Formation of the Cation-Exchanged Hole Transporting Layer

Abstract: In search of a viable way to enhance the power conversion efficiency (PCE) of quantum dot-sensitized solar cells, we have designed a method by introducing a hole transporting layer (HTL) of p-type CuS through partial cation exchange process in a postsynthetic ligand-assisted assembly of nanocrystals (NCs). High-quality CdSe and CdSSe gradient alloy NCs were synthesized through colloidal method, and the charge carrier dynamics was monitored through ultrafast transient absorption measurements. A notable increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Formation of the alloy structure removes the defect states within the NCs limiting the charge carrier trapping process. [28,31,39] In this work, with the help of ultrafast spectroscopy and photovoltaic measurements on homogeneous alloyed CdZnX NCs we have further shown here that they are better candidates for solar cell application compared to CdX NCs as they do not suffer from interfacial traps. These observations have been summarized in Scheme 1 below.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Formation of the alloy structure removes the defect states within the NCs limiting the charge carrier trapping process. [28,31,39] In this work, with the help of ultrafast spectroscopy and photovoltaic measurements on homogeneous alloyed CdZnX NCs we have further shown here that they are better candidates for solar cell application compared to CdX NCs as they do not suffer from interfacial traps. These observations have been summarized in Scheme 1 below.…”
Section: Resultssupporting
confidence: 54%
“…[15,31,[36][37][38][39][40][41] Briefly, TiO 2 photoanodes with transparent layer were prepared through doctor blade technique followed by annealing at 450°C for 30 minutes. [15,31,[36][37][38][39][40][41] Briefly, TiO 2 photoanodes with transparent layer were prepared through doctor blade technique followed by annealing at 450°C for 30 minutes.…”
Section: Device Fabrication For Solar Cellsmentioning
confidence: 99%
“…However, organic hole‐transporting materials are costly and synthetically difficult to prepare, inorganic hole‐transporting materials, on the other hand, are cheap and easy to deposit. We recently demonstrated that CuS is a hole‐transporting layer that can effectively enhance the PCE of QDSSCs in case of post‐synthetic, ligand‐assisted assembly of NCs on TiO 2 . CdSe and two different CdSeS NCs were synthesized and characterized through steady‐state and time‐resolved spectroscopy (Figure ).…”
Section: How Carrier Dynamics Can Benefit Qdscsmentioning
confidence: 99%
“…We recently demonstrated that CuS is ah oletransporting layer that can effectively enhance the PCE of QDSSCs in case of post-synthetic,l igand-assisted assembly of NCs on TiO 2 . [39] CdSe and two different CdSeS NCs were synthesized and characterized through steady-state and time-resolved spectroscopy (Figure 9).…”
Section: Smooth Hole Transportmentioning
confidence: 99%
See 1 more Smart Citation